Impact of permission rule on determining the inherent jurisdiction of iranian family courts - SADEGHI, M.; FASIHIZADEH, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The importance of the family institution requires that family lawsuits be dealt with in a specialized court, indicating the considerable importance of discussing the inherent jurisdiction of this judicial body. Therefore, to legitimize and consolidate family foundations, it is necessary to define the concept of family based on the Molazemeh Rule, so that the goals of the Iranian legislature, which include facilitating the formation of the family institution, protecting the sanctity. Relationships of family members and preventing the disruption of the said institution can be achieved by setting forth family-related matters and components in this exclusive judicial body.